REMEDIASI MISKONSEPSI TENTANG KALOR MENGGUNAKAN MODEL PEMBELAJARAN INTERACTIVE DEMONSTRATION UNTUK PESERTA DIDIK SMKN 7 - Krisida Krisida; Haratua Tiur Maria Silitonga; Syaiful B Arsyid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study aimed to determine the effectiveness of the use of learning model Interactive Demonstration in the remediation of misconceptions about heat using the learning model interactive demonstration to students of SMK Negeri 7 Pontianak. This research used Pre-Experimental Design method with One Group Pretest-Posttest Design. The sample of this research is students of class XII RPL consisted of 39 students selected by random sampling technique with an intact group. Data collection tool in the form of 9 questions in the form of multiple choice. The average percentage of the number of learners misconceptions 79,27%. Based on the Mc Nemar, large changes in the conception of learners obtained  (13,09) >  (3.84) for dk = 1 and α = 5%, there is a change in the conception of learners that significant after the given remediation. The value of the DQM obtained amounted to 79% as high, then the learning model Interactive Demonstration of effective in remediate misconceptions of learners. This research expected can be used as an alternative remediation activity in addressing misconceptions experienced by learners. Keywords: Heat,  Interactive Demonstration , Misconception, Remediation